2010
DOI: 10.1111/j.1469-7998.2009.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Even mortality patterns of the two sexes in a polygynous, near‐monomorphic species: is there a flaw?

Abstract: The chamois Rupicapra rupicapra has been termed a highly polygynous species, with a great male competition for mating. If so, a lower survival should be expected for the male sex. From 1986 to 2000, 1801 carcasses of chamois were collected in the Maritime Alps Regional Park, Italy, where a protected, healthy, stable population of chamois occurred (c. 12 individuals 100 ha À1 ). Each year, population structure from carcasses was consistent with that from the count carried out on the preceding year on live indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 51 publications
5
38
0
Order By: Relevance
“…The very low survival of PNGP males was likely partly due to their advanced age, but it was much lower than the 75-80% survival reported for old male Pyrenean chamois (Loison et al 1999). Overall, sex-and age-specific survival data for PNAM and PNM confirm earlier reports that adult chamois mortality does not differ substantially according to sex (Loison et al 1999;Bocci et al 2010).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The very low survival of PNGP males was likely partly due to their advanced age, but it was much lower than the 75-80% survival reported for old male Pyrenean chamois (Loison et al 1999). Overall, sex-and age-specific survival data for PNAM and PNM confirm earlier reports that adult chamois mortality does not differ substantially according to sex (Loison et al 1999;Bocci et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…We examined its consequences for the survival of adult (2-9 years old) and senescent (10 years and older) chamois in three populations. We expected that the harsh winter would substantially lower the survival of senescent but not of prime-aged females and that males would not suffer much higher mortality than females, as previously reported for this species (Loison et al 1999;Bocci et al 2010). …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We monitored 35 animals older than 15 years, and 20 animals older than 18 years, suggesting that chamois are an unusually long-lived ungulate. The high maximum longevity of individuals within our population (21 years for males, 22 years for females), compared to previously recorded figures of 17 years in both sexes (Bocci et al 2010) seems unlikely to be due to methodological reasons, as in Table 4 Mean estimate, standard error and 95% CI of sex-and age-specific survival rates calculated from models #4 [˚(sex + time) p(age · sex)] and #7 [˚(age + time) p(age · sex)] for 116 Alpine chamois over 13 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) both cases age was estimated by counting growth rings. Likewise, Loison et al (1994) found high survival in female chamois older than 3.5 years (0.95, 95% CI = 0.93-0.99), suggesting that survival senescence in chamois may be weaker than in other ungulates.…”
Section: Discussionmentioning
confidence: 49%
“…6% in January, Garel et al 2009; 4% in spring, Rughetti and Festa-Bianchet 2011). To date only two studies, based on life tables analysis, investigated the sex-specific survival of Alpine chamois (Schröder 1971;Bocci et al 2010), producing conflicting results.…”
Section: Introductionmentioning
confidence: 93%